2022
DOI: 10.3389/fnut.2022.1031594
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous yeast can increase the phenolic acid and volatile ester compounds in Petit Manseng wine

Abstract: IntroductionIndigenous yeasts are generally found in grapes, vineyards, and natural environments. Sequential inoculation and fermentation with non-Saccharomyces cerevisiae yeast (H30) and Saccharomyces cerevisiae (YT13) also improve the flavor of wine.MethodsThis study sequentially inoculated fermented Petit Manseng and natural grape juice with native H30 and YT13 selected from vineyards in Yantai, China.Results and discussionThe sensory characteristics of Petit Manseng wine were evaluated by detecting the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Yeasts from different regions also have unique characteristics. Wang et al [ 13 ] fermented small ginseng and grape juice via sequential inoculation with native Yantai yeasts H30 and YT 13, and the results showed that the lactic acid contents of the natural wines fermented with H30 and YT 13, respectively, were higher than that of the control group fermented with ferulic acid in a single fermentation, while the mixed fermentation group was also found to contain butyrolactone and propionic acid anthocyanins, which increased the complexity of the aroma of small ginseng wine, and provided a high-quality yeast resource for the production of white wine with unique regional characteristics. Liu et al [ 14 ] extracted four strains of aromatic yeast from citrus peels from Sichuan after analyzing and identifying the morphological, physiological, and biochemical characteristics and ITS sequence features, enabling them to produce a strong aroma.…”
Section: Source Of Aroma-producing Yeastmentioning
confidence: 99%
“…Yeasts from different regions also have unique characteristics. Wang et al [ 13 ] fermented small ginseng and grape juice via sequential inoculation with native Yantai yeasts H30 and YT 13, and the results showed that the lactic acid contents of the natural wines fermented with H30 and YT 13, respectively, were higher than that of the control group fermented with ferulic acid in a single fermentation, while the mixed fermentation group was also found to contain butyrolactone and propionic acid anthocyanins, which increased the complexity of the aroma of small ginseng wine, and provided a high-quality yeast resource for the production of white wine with unique regional characteristics. Liu et al [ 14 ] extracted four strains of aromatic yeast from citrus peels from Sichuan after analyzing and identifying the morphological, physiological, and biochemical characteristics and ITS sequence features, enabling them to produce a strong aroma.…”
Section: Source Of Aroma-producing Yeastmentioning
confidence: 99%